Delayed Re-epithelialization After Epithelium-Off Crosslinking: Predictors and Impact on Keratoconus Progression - Bonzano, Chiara; Cutolo, Carlo Alberto; Musetti, Donatella; Di Mola, Ilaria; Pizzorno, Chiara; Scotto, Riccardo; Traverso, Carlo Enrico (Frontiers in Medicine, 2021)
Purpose: To investigate the demographic and corneal factors associated with the occurrence of delayed reepithelialization (DRE) after epithelium-off crosslinking (epi-off CXL). Design:Retrospective case series. Methods:A chart review was performed to identify patients treated with epi-off CXL. DRE was defined as a corneal epithelial defect detected by fluorescein staining that persisted for more than 10 days. Slit-lamp examination, anterior segment optical coherence tomography, corneal topography, and corneal in vivo confocal microscopy (IVCM) were always performed preoperatively and at each follow-up visit (1, 3, 6, 12 months). A generalized estimating equation was used to assess the baseline factors associated with DRE. Results:Data from 153 eyes were analyzed. The mean age of patients was 24.9 ± 8.5 years, and 47 (30.7%) were women. The average reepithelization time was 4.7 ± 1.8 days. Six eyes (3.9%) experienced DRE. In the multivariate model, both the age of the patient (OR = 1.30; p = 0.02) and the corneal steepest meridian (OR = 0.44, p = 0.047) were associated with DRE. Baseline nerve count was also associated with DRE (0.87, p = 0.03). Male gender was associated with a slower early nerve regrowth (1–6 months) (p = 0.048), but not with the occurrence of DRE (p = 0.27). Preoperative central corneal thickness was not related to DRE (p = 0.16). DRE was not associated with keratoconus progression after epi-off CXL (p = 0.520). Conclusions:The association between DRE and age may reflect the age-related decrease in the corneal healing response. Also, low baseline corneal nerve count is associated with DRE. Gender seems to affect reinnervation measured by IVCM but not the reepithelization time. DRE does not seem to affect the efficacy of epi-off CXL.